2015
DOI: 10.1534/genetics.115.177170
|View full text |Cite
|
Sign up to set email alerts
|

Selective Advantages of a Parasexual Cycle for the YeastCandida albicans

Abstract: The yeast Candida albicans can mate. However, in the natural environment mating may generate progeny (fusants) fitter than clonal lineages too rarely to render mating biologically significant: C. albicans has never been observed to mate in its natural environment, the human host, and the population structure of the species is largely clonal. It seems incapable of meiosis, and most isolates are diploid and carry both mating-type-like (MTL) locus alleles, preventing mating. Only chromosome loss or localized loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 89 publications
(136 reference statements)
1
28
0
1
Order By: Relevance
“…Amongst all putative sorghum orthologs, 9 were in common across a minimum of two species, leading to 111 unique orthologs in sorghum identified as seed size candidate genes (Figure 1). Four seed size candidate genes in sorghum from Zhang et al (2015) with one overlapped with the 111 seed size orthologs were also taken into consideration, resulting in a final list of 114 seed size candidate genes.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst all putative sorghum orthologs, 9 were in common across a minimum of two species, leading to 111 unique orthologs in sorghum identified as seed size candidate genes (Figure 1). Four seed size candidate genes in sorghum from Zhang et al (2015) with one overlapped with the 111 seed size orthologs were also taken into consideration, resulting in a final list of 114 seed size candidate genes.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, opaque cells represent a more metabolically specialized cell state, exhibiting greater fitness than white cells only under selective conditions. Opaque cells are the mating competent form of the species, which is thought to be relatively rare in nature (8789), but may provide a competitive advantage under some conditions (90, 91). Our profiling data support the designation of opaque cells as being a specialized cell type, but whose properties further extend the fitness and phenotypic attributes of the organism, thereby enabling adaptation to a wider range of environmental situations.…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans, a pathogenic yeast species that is not known to naturally mate but does show population genetic signs of recombination [49], can be induced to mate under certain circumstances using the parasexual cycle [48]. A recent study using mouse model experiments showed that novel parasexually produced genotypes can be obtained that are fitter than the parental strains [50]. Unfortunately it is not known if parasex occurs in nature, because in most Ascomycota it may be limited to species which are vegetatively compatible (usually genetically identical mycelia) and thus is difficult to detect.…”
Section: Sexual Reproduction and Recombinationmentioning
confidence: 99%